LONG-TERM MONITORING AND MODELING EXTENT OF AGRICULTURAL-DERIVED NITRATE CONTAMINATION IN SHALLOW GROUNDWATER SYSTEMS OF THAILAND AND POSSIBLE LINKS TO SURFICIAL SOURCES - Aksara Putthividhya; Sasin Jirasirirak; Ratchapon Pipitsombat (International Association of Lowland Technology, 2020)
Undesirable chemical dissolution in groundwater can cause very serious health problems, whether the chemicals are naturally occurring or anthropogenic origin. In Thailand, soil and groundwater pollution has continued to increase due to population growth and agricultural development in the past decades. Nitrate contamination in groundwater has long been discovered in Thailand, arising from intensive agriculture with excessive fertilization. Contaminant transport modeling efforts in this paper were made to extend further long-term monitoring of nitrate contamination level in Suphanburi and Kanchanaburi and investigate any links of contaminant hotspots in groundwater with possible surface sources for further planning and management. Analysis of 160 groundwater samples collected from domestic and monitoring wells at various depths (100 samples from less than 30 m deep, and 60 samples from more than 30 m deep) for nitrogen (as NO3-), K, sulphate (as SO42-) and other chemicals was carried out. Aqueous NO3- concentration levels in groundwater varied from as low as 0.18 to maximum of 151 mg/L (maximum concentration level = 45 mg/L; Ministry of Natural Resources and Environment Thailand). Consistent K and NO3- patterns from monitoring and production wells in the study area revealed that nitrate source was agricultural origin rather than sewer leakage. 30% of shallow groundwater samples (< 30 m) were detected with higher nitrate concentration than MCL whereas only 23% of groundwater samples taken from > 30 m deep were found contaminated, suggesting the direct association of major nitrate contamination in groundwater aquifer with their potential agricultural sources above ground (i.e., vegetable farming and rice paddy field). The numerical model was developed to generate regional groundwater flow characteristics and piezometric level distributions using the USGS 3D finite-difference code MODFLOW-2000. The well-calibrated regional groundwater flow model was coupled with MT3D to simulate laboratory- and regional-scaled aqueous nitrate transport as well as to project far-future nitrate migration characteristics. Simulated nitrate plume mobility can extend more than 50 km further downstream from the hot spots, suggesting that systematic monitoring well network as well as remediation programs are required for contaminant risk analysis and reduction. Future projections of nitrate transport model can be used to test “what-if” scenarios to improve effectiveness and efficiency of potential nitrate management, planning, and monitoring programs.